Retrogene duplication and expression patterns shaped by the evolution of sex chromosomes in malaria mosquitoes - Miller, Duncan; Chen, Jianhai; Liang, Jiangtao; Betrán, Esther; Long, Manyuan; Sharakhov, Igor V. (Genes)
Genes that originate during evolution are an important source of novel biological functions. Retrogenes are functional copies of genes produced by retroduplication and as such are located in different genomic positions. To investigate retroposition patterns and retrogene expression, we computationally identified interchromosomal retroduplication events in nine portions of the phylogenetic history of malaria mosquitoes, making use of species that do or do not have classical sex chromosomes to test the roles of sex-linkage. We found 40 interchromosomal events and a significant excess of retroduplications from the X chromosome to autosomes among a set of young retrogenes. These young retroposition events occurred within the last 100 million years in lineages where all species possessed differentiated sex chromosomes. An analysis of available microarray and RNA-seq expression data for Anopheles gambiae showed that many of the young retrogenes evolved male-biased expression in the reproductive organs. Young autosomal retrogenes with increased meiotic or postmeiotic expression in the testes tend to be male biased. In contrast, older retrogenes, i.e., in lineages with undifferentiated sex chromosomes, do not show this particular chromosomal bias and are enriched for female-biased expression in reproductive organs. Our reverse-transcription PCR data indicates that most of the youngest retrogenes, which originated within the last 47.6 million years in the subgenus Cellia, evolved non-uniform expression patterns across body parts in the males and females of An. coluzzii. Finally, gene annotation revealed that mitochondrial function is a prominent feature of the young autosomal retrogenes. We conclude that mRNA-mediated gene duplication has produced a set of genes that contribute to mosquito reproductive functions and that different biases are revealed after the sex chromosomes evolve. Overall, these results suggest potential roles for the evolution of meiotic sex chromosome inactivation in males and of sexually antagonistic conflict related to mitochondrial energy function as the main selective pressures for X-to-autosome gene reduplication and testis-biased expression in these mosquito lineages.